Participación de la esfingosina cinasa en la diferenciación celular y organización tisular - Santacreu, Bruno Jaime (2018)
Sphingosine kinase (SphK) biosynthesizes sphingosine-1-phosphate (S1P). S1P is a bioactive sphingolipid and has been shown to exert a variety of biological responses intracellularly or through extracellular specific receptors. Renal epithelial cell differentiation is a process that involves the mesenchymal epithelium transition (MET). During the MET, mesenchymal cells become polarized and establish cell junctions. The goal of this thesis was to study the role of S1P in the MET process of renal epithelial cells, as well as in the homeostasis once the differentiated state has already been established. We found a synchronization between the SphK / S1P pathway during MET, generated by a decrease in the activity of the SphK while cell differentiation progresses. In the less differentiated stages this was necessary to produce an inhibition of sphingolipids synthesis, to avoid ceramide accumulation and to correctly deliver of the adherens junction proteins. Whereas, the low global level of S1P in differentiated cells mobilizes the S1P(2) receptor to the plasma membrane. Moreover, it allows locally increases of S1P by SphK2 to mediate apoptotic cell extrusion. Thus, this synchronization guarantees the integrity of the epithelial tissue.